2018
DOI: 10.4103/ijpsym.ijpsym_59_18
|View full text |Cite
|
Sign up to set email alerts
|

Addiction-like Behavior Associated with Mobile Phone Usage among Medical Students in Delhi

Abstract: Background: Mobile phone addiction is a type of technological addiction or nonsubstance addiction. The present study was conducted with the objectives of developing and validating a mobile phone addiction scale in medical students and to assess the burden and factors associated with mobile phone addiction-like behavior. Materials and Methods: A cross-sectional study was conducted among undergraduate medical students aged ≥18 years studying in a medical college in New De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 19 publications
5
71
2
2
Order By: Relevance
“…Methodological heterogeneity arising from the different questionnaires used for assessment of mobile phone addiction precludes an accurate comparison with our study findings. [ 3 16 17 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodological heterogeneity arising from the different questionnaires used for assessment of mobile phone addiction precludes an accurate comparison with our study findings. [ 3 16 17 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, Basu et al ., revealed that as such no statistically significant difference exist among young age individuals and other groups for nomophobia. [ 16 17 21 28 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone addiction is so prevalent that it is already considered to be like any other addiction to harmful substances. Therefore, it is a public health problem [9], which is why, because of the excessive use of this device [10] and the dependence that this technology generates [11], a new pathology known as nomophobia is emerging [12] and being cataloged as a clinical disorder [13].…”
Section: Introductionmentioning
confidence: 99%
“…) due to the fact that the main object of study was not nomophobia (n = 14)[3,6,[8][9][10]21,[50][51][52][53][54][55][56][57].…”
mentioning
confidence: 99%
“…8% in Anhui Province, China55 ; 39.9% in Delhi, India56 ; and 36.5% in Jeddah, Saudi Arabia,57 with differences in gender). In the current study, the results are unclear whether smartphone addiction is a primary problem, a response to 1 or more subscales of medical student burnout, or a proxy for other issues.Paradoxically, the ubiquitous nature of smartphones may be exploited as a viable tool for intervention.…”
mentioning
confidence: 99%